Centralized Admission Systems and School Segregation: Evidence from a National Reform - Macarena Kutscher; Shanjukta Nath; Sergio Urzua (Institute of Labor Economics (IZA), 2020)
This paper investigates whether centralized admissions systems can alter school segregation. We take advantage of the largest school-admission reform implemented to date: Chile's SAS, which in 2016 replaced the country's decentralized system with a Deferred Acceptance algorithm. We exploit its incremental implementation and employ a Difference-in-Difference design. Using rich administrative student-level records, we find the effect of SAS critically depends on pre-existing levels of residential segregation and local school supply. For instance, districts with prominent provision of private education experience an uptick in school segregation due to SAS. Migration of high-SES students to private schools emerges as a key driver.
Keywords: I20; I24; I28; 330; education; inequality; segregation